2023
DOI: 10.3390/biomedicines11123233
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Pathways in Overweight and Obese Persons as a Potential Mechanism for Cognitive Impairment and Earlier Onset Alzeihmer’s Dementia in the General Population: A Narrative Review

Alexandru Dan Costache,
Bogdan Emilian Ignat,
Cristina Grosu
et al.

Abstract: The overweight status or obesity can be confirmed through classical methods such as the body mass index (BMI) and the waist-to-hip ratio (WHR). Apart from metabolic issues such as atherosclerosis, liver steatosis, or diabetes mellitus, long-term obesity or overweight status can pose a risk for cardiovascular and neurovascular complications. While some acute adverse events like coronary syndromes of strokes are well-documented to be linked to an increased body mass, there are also chronic processes that, due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 208 publications
0
2
0
Order By: Relevance
“…A growing body of research has demonstrated bidirectional relationships between diet quality and mental health outcomes [52]. For example, several studies indicate that diets high in processed foods, saturated fats, and refined carbohydrates can negatively impact mood and cognition, whereas diets rich in fruits, vegetables, whole grains, and omega-3 fatty acids are associated with a reduced risk of depression and other psychiatric disorders [5,10,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research has demonstrated bidirectional relationships between diet quality and mental health outcomes [52]. For example, several studies indicate that diets high in processed foods, saturated fats, and refined carbohydrates can negatively impact mood and cognition, whereas diets rich in fruits, vegetables, whole grains, and omega-3 fatty acids are associated with a reduced risk of depression and other psychiatric disorders [5,10,53].…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies indicate that diets high in processed foods, saturated fats, and refined carbohydrates can negatively impact mood and cognition, whereas diets rich in fruits, vegetables, whole grains, and omega-3 fatty acids are associated with a reduced risk of depression and other psychiatric disorders [5,10,53]. The proposed mechanisms for these effects include modulation of the gut microbiota, inflammation, oxidative stress, and neuroplasticity through dietary components that influence immune and metabolic pathways [52]. Further elucidating the relationship between diet and mental health in patients with serious mental illnesses may reveal modifiable risk factors and opportunities for nutritional interventions.…”
Section: Discussionmentioning
confidence: 99%